EXPLORING THE RELATIONSHIP BETWEEN INTERPROFESSIONAL TEAM CLIMATE AND JOB SATISFACTION AMONG PHYSICIANS, DENTISTS, NURSES, PHARMACISTS, RESPIRATORY THERAPISTS, AND HOSPITAL MANAGERS IN A SAUDI ARABIAN ARMED FORCES HOSPITAL - Waleed Abdullah Ahmed Alzahrani, Abdulaziz Mohammed Ahmed Alghamdi, Mamdouh Ali Ibrahim Alzahrani, Mohammed Matar Muidh Alshamrani, Mansour Farhan Ayed Alhazmi, Rashed Abdullah Jazaa Alharbi (Chelonian Research Foundation, 2024)
Objective: To explore the relationship between interprofessional team climate and job satisfaction among healthcare professionals in a Saudi Arabian military hospital. Methods: A cross-sectional survey study was conducted at Hafr Al-Batin Armed Forces Hospital in Saudi Arabia. A total of 248 healthcare professionals, including physicians, dentists, nurses, pharmacists, respiratory therapists, and hospital managers, completed the Team Climate Inventory (TCI) and the Job Satisfaction Survey (JSS). Pearson correlation and multiple regression analyses were performed to assess the relationship between TCI and JSS scores. Results: A significant positive correlation was found between overall TCI and JSS scores (r=0.74, p<0.001). Among the TCI subscales, vision (r=0.69, p<0.001), participative safety (r=0.67, p<0.001), task orientation (r=0.65, p<0.001) and support for innovation (r=0.61, p<0.001) had significant correlations with job satisfaction. Multiple regression analysis revealed that the TCI subscales collectively explained 59.4% of the variance in job satisfaction (R2=0.594, F(4,243)=89.38, p<0.001). Vision was the strongest predictor of job satisfaction (β=0.32, p<0.001), followed by participative safety (β=0.26, p<0.001), task orientation (β=0.22, p<0.001) and support for innovation (β=0.17, p<0.01). Conclusions: A positive team climate is strongly associated with higher job satisfaction among interprofessional healthcare teams in a Saudi military hospital setting. Strategies to enhance shared vision, psychological safety, commitment to excellence and support for innovation may promote job satisfaction and staff retention. Further research is needed to identify interventions to foster these team attributes.